Use of PETRA-MRA to assess intracranial arterial stenosis: Comparison with TOF-MRA, CTA, and DSA - Niu, Junxia; Ran, Yuncai; Chen, Rui; Zhang, Feifei; Lei, Xiaowen; Wang, Xiao; Li, Tengfei; Zhu, Jinxia; Zhang, Yong; Cheng, Jingliang; Zhang, Yan; Zhu, Chengcheng (Frontiers in Neurology, 2023)
Background and Purpose：Noninvasive and accurate assessment of intracranial arterial stenosis (ICAS) is important for the evaluation of intracranial atherosclerotic disease. This study aimed to evaluate the performance of 3D pointwise encoding time reduction magnetic resonance angiography (PETRA-MRA), and compare its performance with that of 3D time-of-flight (TOF) MRA and computed tomography angiography (CTA), using digital subtraction angiography (DSA) as the reference standard in measuring the degree of stenosis and lesion length. Materials and Methods: This single-center, prospective study included a total of 52 patients (mean age 57 ± 11 years, 27 males, 25 females) with 90 intracranial arterial stenoses who underwent PETRA-MRA, TOF-MRA, CTA, and DSA within 1 month. The degree of stenosis and lesion length were measured independently by 2 radiologists on these 4 datasets. Severe stenosis was defined as a single lesion with ＞70% diameter stenosis. The continuous variables were compared using paired t test or Wilcoxon signed rank test. The intraclass correlation coefficients (ICCs) were used to assess the agreement between MRAs/CTA and DSA and inter-reader variabilities. When the difference between MRAs/CTA and DSA was statistically significant in the degree of stenosis, the measurement of MRAs/CTA was larger than DSA that referred to the overestimation of MRAs/CTA for the degree of stenosis. Results: The 4 imaging methods exhibited excellent inter-reader agreement [intraclass correlation coefficients (ICCs) > 0.80]. PETRA-MRA was more consistent with DSA than with TOF-MRA and CTA in measuring the degree of stenosis (ICC = 0.94 vs 0.79 and 0.89) and lesion length (ICC = 0.99 vs 0.97 and 0.73). PETRA-MRA obtained highest specificity and positive predictive value (PPV) than TOF-MRA and CTA for detecting stenosis >50% and stenosis >75%. TOF-MRA and CTA overestimated considerably the degree of stenosis compared with DSA (63.0% ± 15.8% and 61.0% ± 18.6% vs 54.0% ± 18.6%, P < 0.01, respectively), whereas PETRA-MRA did not overestimate (P = 0.13). Conclusion: PETRA-MRA is more accurate than TOF-MRA and CTA for the evaluation of intracranial stenosis and lesion length. PETRA-MRA is a promising noninvasive tool for ICAS assessment.